A Comparative Study of Coping Strategies and the Features of Interpersonal Relations and Life Orientations of People with Congenital and Acquired Diseases of the Musculoskeletal System. Issue 11 (1st November 2016) - Romanova, E.V.; Tolkacheva, O.N.
Abstract : The article presents the results of a comparative study of the features of the coping strategies, life orientations, and interpersonal relations of disabled people with acquired and congenital diseases of the musculoskeletal system. The authors discovered differences in interpersonal behavior in the area of control, and they revealed factors that affect how persons with acquired disabilities and those who have been disabled since childhood develop life orientations.